Optimized Design, Monitoring System Development and Experiment for a Long-Belt Finger-Clip Precision Corn Seed Metering Device - Tang, Han; Xu, Changsu; Wang, Ziming; Wang, Qi; Wang, Jinwu (Frontiers in Plant Science, 2022)
To solve multiple problems, such as the poor seeding process stability in the conventional finger-clip precision corn seed metering device and the inability to monitor the seeding effect, a long-belt finger-clip precision seed metering device was optimized and designed. The overall structure and working principle were described, and the mechanism of smooth transport and delivery was analyzed. A diffuse reflection photoelectric sensor and rectangular optical fiber sensor were used to monitor the number of corn seeds in the seeding process, and the states of multiple and miss seeding were calculated. A corn seeding quality monitoring system was designed. In this study, the seed metering performance of the long-belt finger-clip precision seed metering device was compared to that of the conventional finger-clip precision corn seed metering device. It was shown that the reseeding index, the miss-seeding index and the coefficient of variation can be effectively reduced with increasing seed metering tray speed. At the maximum speed of 65r/min, the qualified index increased from 75.75 to 84.70%, the reseeding index decreased from 13.66 to 8.49%, the miss-seeding index decreased from 10.59 to 6.81%, and the coefficient of variation decreased from 20.69 to 6.83%. The variations of these four evaluation parameters with the seed metering tray rotating speed were analyzed. Furthermore, the effects of the seeding frequency and seeding speed on the four evaluation parameters were studied through single factor and variance analyses. The results showed that the relative errors of the qualified index, the reseeding index, the miss-seeding index and the seeding amount increased gradually with the increase in the seed metering tray rotating speed, and the monitoring accuracy of the sensor decreased gradually. The accuracy of sensor monitoring decreased with increasing seeding frequency and seeding speed. This study provides an optimized scheme for the smooth delivery and movement of conventional seed metering devices and provides a technical reference for the development and design of monitoring systems with multiple index and the miss-seeding index of seed metering devices.